Procalcitonin Is Not a Reliable Biomarker of Bacterial Coinfection in People With Coronavirus Disease 2019 Undergoing Microbiological Investigation at the Time of Hospital Admission. (1st May 2022) - Relph, Katharine A; Russell, Clark D; Fairfield, Cameron J; Turtle, Lance; de Silva, Thushan I; Siggins, Matthew K; Drake, Thomas M; Thwaites, Ryan S; Abrams, Simon; Moore, Shona C; Hardwick, Hayley E; Oosthuyzen, Wilna; et al.
Abstract: Admission procalcitonin measurements and microbiology results were available for 1040 hospitalized adults with coronavirus disease 2019 (from 48 902 included in the International Severe Acute Respiratory and Emerging Infections Consortium World Health Organization Clinical Characterisation Protocol UK study). Although procalcitonin was higher in bacterial coinfection, this was neither clinically significant (median [IQR], 0.33 [0.11–1.70] ng/mL vs 0.24 [0.10–0.90] ng/mL) nor diagnostically useful (area under the receiver operating characteristic curve, 0.56 [95% confidence interval, .51–.60]).